China baseline coal-fired power plant with post-combustion CO2 capture: 1. Definitions and performance. (November 2018) - Cui, Qian; Lu, Haoren; Li, Chufu; Singh, Surinder; Ba, Liming; Zhao, Xinglei; Ku, Anthony Y.
Highlights: Baseline power plant models are essential for understanding the cost of CO2 capture. Power plants in China have distinct hardware and operating conditions. A set of "baseline China plants with CO2 capture" are proposed. The biggest drivers for differences are steam cycle hardware and dry cooling. Abstract: Global efforts to advance CO2 capture technologies have produced a strong base of field experience and modeling capability to inform efforts to deploy this technology in China. For example, the U.S. Department of Energy has published bituminous coal baseline reference cases to provide a consistent set of assumptions for modeling the performance of coal power plants equipped with CO2 capture technology in the United States. In China, there are some important features of power plant construction and operation, such as dry cooling in some plants, different grade coal, and low load operation, that must be accounted for in analyzing the performance of CO2 capture-enabled power plants. Moreover, unique aspects of the policy landscape in China, such as an openness to partial capture solutions in the near-term, introduce some flexibility in deployment strategy. In this study, we analyze the impacts of these features on plant performance and we propose a set of "baseline China plants" based on industrial experience to serve as reference cases for analyzing deployment scenarios for post-combustion CO2 capture at coal-fired power plants in China. This paper focuses specifically on the performance aspects of the technoeconomic analysis. Costs are addressed in a companion paper. The most significant factors responsible for differences in power plant efficiency were fuel quality and differences in steam cycle hardware and operation. The impact of dry cooling was also significant. Our reference cases are broadly consistent with previous studies of this topic and help to clarify the contributions of different factors when comparing the performance of CO2 capture for power plants in the US and China.